Wpływ cen i dopłat bezpośrednich na poziom dochodów gospodarstw rolnych po akcesji Polski do Unii Europejskiej - Chmielewska, Barbara (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Poland's accession to the EU improved economic situation of agricultural families. Improvement came out of prices regulations and different forms of support, which are part of CAP implemented in Poland. The most noticeable for farm families are direct payments. Adventageous prices impact is decreased by demand and share diminishing of raw material prices in final product prices. However, direct payments were important for improving economic situation especially for this with large area. This kind of support has got only irrelevant impact on farm households with small area. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 52-60